ARTICLE AND ARTICLES TYPES - Raxmonova Samira Otabekovna; Yuldasheva Dilnoza Bekmurodovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
An article is a written work that provides information, insights, or analysis on a particular subject. Articles can be found in academic journals, magazines, newspapers, and online platforms. They serve to inform, educate, or entertain readers by presenting facts, viewpoints, or research findings. This article explores different types of articles and their characteristics, offering insight into their structure and purpose in various contexts.